Ethical climate (EC) and perceived organizational support (POS) on workplace deviance behavior (WDB) among academicians in Malaysia public university - Abu Samah, Nur Asyira; Musa, Siti Nur Syuhada; Umar Baki, Nordahlia (Human Resource Management Academic Research Society, 2024)
Deviant behavior in the workplace has garnered interest from numerous researchers and human resource managers due to its significant impact on employee well-being and organizational productivity. The government has undertaken various initiatives to enhance the integrity of academicians in public higher education institutions and address workplace misconduct. However, these efforts have not fully succeeded in preventing lecturers from engaging in inappropriate behavior, as evidenced by ongoing reports of misconduct and disciplinary actions taken against them. This study is based on a review of past research, which has shown limited emphasis on the organizational factors contributing to deviant behavior among academicians in public higher education institutions. Therefore, this research aimed to investigate the effects of ethical climate and perceived organizational support on deviant behavior in the workplace. It is hoped that the findings of this research will contribute to the literature on significant factors influencing workplace deviance among academicians in Malaysian public universities.